2016
DOI: 10.1001/jamainternmed.2015.8248
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Quality of Urgent Health Care Provided During Commercial Virtual Visits

Abstract: Importance Commercial virtual visits are an increasingly popular model of care for the management of common, acute illnesses. In commercial virtual visits, patients access a website to be connected synchronously—via videoconference, telephone, or webchat—to a physician with whom they have no prior relationship. There has been no assessment of whether the care delivered through those websites is similar, or whether quality varies among the sites. Objective To assess the variation in quality of care among virt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 18 publications
3
45
0
Order By: Relevance
“…Indeed, substantial variation in the quality of telemedicine care has been reported. 25,26 To date, no study has described a large group of physicians who practice DTC telemedicine. The overwhelming majority of physicians in our sample were trained at US medical schools and were generalists.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, substantial variation in the quality of telemedicine care has been reported. 25,26 To date, no study has described a large group of physicians who practice DTC telemedicine. The overwhelming majority of physicians in our sample were trained at US medical schools and were generalists.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Mehrotra et al [ 5 ] found that e-visits had roughly the same treatment outcomes as in-person visits for sinusitis and urinary tract infections, but e-visits had higher rates of antibiotic prescription. Schoenfeld et al [ 6 ] found considerable variation in the quality of care provided by commercial telemedicine companies. As more patients are seen remotely and indications for telemedicine become more complex, we need to train physicians to offer digital care on par with in-person consultation.…”
Section: Ensuring High-quality Carementioning
confidence: 99%
“…Real-time telemedicine can be delivered between two clinic sites (e.g., hospital to remote hospital/clinic) or directly between a care provider and the patient at home or work. Direct-to-consumer (DTC) telemedicine can provide immediate and convenient access to a care provider that usually costs less than a standard in-person urgent care or emergency room visit [3]. DTC telemedicine has also been shown to increase access to care to those without a primary care provider [4, 5].…”
Section: Introductionmentioning
confidence: 99%